2015
DOI: 10.1007/s40261-015-0275-9
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Nucleoside Reverse Transcriptase Inhibitors in Adults Receiving Continuous Veno-Venous Hemofiltration

Abstract: Clinicians should utilize these recommendations in the context of each individual patient, taking into consideration patient-specific factors and severity of illness. Future pharmacokinetic research correlating plasma and intracellular concentrations of NRTIs during CVVH is warranted to elucidate appropriate dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Increased clearance of NRTIs may lead to decreased drug concentrations, which impact ART efficacy and increase risk for drug resistance [ 21 , 83 ]. Proposed guidelines on dosing of NRTIs based on CVVH flow rate (L/hour) have been published, but later pharmacokinetic studies demonstrated inaccuracies in this approach, with only 41% of NRTIs providing a favorable pharmacokinetic profile [ 83 , 85 ]. Further studies are needed to demonstrate safety and efficacy of renally eliminated antiretroviral medications in the setting of increased renal clearance.…”
Section: Antiretroviral Interactions With Disease States In Pwh Who A...mentioning
confidence: 99%
“…Increased clearance of NRTIs may lead to decreased drug concentrations, which impact ART efficacy and increase risk for drug resistance [ 21 , 83 ]. Proposed guidelines on dosing of NRTIs based on CVVH flow rate (L/hour) have been published, but later pharmacokinetic studies demonstrated inaccuracies in this approach, with only 41% of NRTIs providing a favorable pharmacokinetic profile [ 83 , 85 ]. Further studies are needed to demonstrate safety and efficacy of renally eliminated antiretroviral medications in the setting of increased renal clearance.…”
Section: Antiretroviral Interactions With Disease States In Pwh Who A...mentioning
confidence: 99%